DINAMIKA DAN PROBLEMATIKA PENDIDIKAN POLITIK DI INDONESIA - Datuzuhriah, Ifa; Amelia Putri, Umi; Sirozi, M. (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
Political education in Indonesia is experiencing complex dynamics influenced by regulatory changes, advances in information technology, and increasing political participation of the younger generation. However, crucial problems include low political literacy, unequal access to political education, the practice of money politics, and polarization that hinders objective political learning. The lack of public understanding of the system and its political rights is a major challenge. Political education that is less oriented towards democratic values, freedom of expression, and tolerance makes society vulnerable to information manipulation and identity politics. This study analyzes these dynamics and problems, identifies the causal factors, and recommends strategies to improve the quality of political education. Low political literacy and unequal access cause a gap in political understanding. The practice of money politics and polarization create an unhealthy political climate, hindering critical and responsible political learning. Therefore, the role of formal and informal educational institutions in instilling democratic citizenship values ??is very important to realize a dignified and sustainable democracy in Indonesia. This study contributes to the understanding of the challenges in building critical and responsible political awareness among the community.